Lack of RNase-sensitive RNA-dependent DNA polymerase activity in the nuclear fraction of Neurospora crassa 74A - D. Mukhopadhyay; N. Williams; S. K. Dutta (Fungal Genetics Reports, 1978)
Lack of RNase-sensitive RNA-dependent DNA polymerase activity in the nuclear fraction of Neurospora crassa 74A